Malaysia’s security concerns: a contemporary assessment - Lai, Yew Meng (Taylor and Francis Inc., 2014)
On the fateful day of 11 February 2013, an approximately 150-strong armed militant group calling themselves the Royal Security Forces of the Sultanate of Sulu and North Borneo breached the far-eastern borders of Sabah, Malaysia, and landed in Lahad Datu to assert what they claimed as their unresolved territorial rights in North Borneo. Dispatched by one of the self-styled heirs to the throne of the now-defunct Sulu Sultanate, the armed intruders camped in at the remote village of Tanduo, located in the dense oil-palm estate of Felda Sahabat, despite repeated appeals from both the Malaysian and Philippine governments for their peaceful withdrawal. Their defi ant stance unavoidably led to a month-long bloody stand-off with the Malaysian security forces that saw seventy-seven casualties, including nine Malaysian servicemen and six civilians. Not only did the ‘Lahad Datu Incident’ shock the nation, it also served as a timely wake-up call for Malaysia to review its national security preparedness in the face of potential and real threats, from within and externally.